Hybrid kinetic facade: fabrication and feasibility evaluation of full-scale prototypes. (2nd November 2022) - Globa, Anastasia; Costin, Glenn; Tokede, Olubukola; Wang, Rui; Khoo, Chin Koi; Moloney, Jules
ABSTRACT: This paper details the design, fabrication and evaluation strategies of the full-scale aluminium panel prototypes developed for a kinetic hybrid facade. The concept of a hybrid facade was proposed as an approach to maximise the value of kinetic intelligent building systems. The overarching research project investigates the potential, feasibility and real-life applications of a hybrid facade that integrates environmental, media and individual micro-control functions in one compound solution operating through autonomous rotating panels. This paper describes the ongoing hybrid facade project's third research stage, focusing on the manufacturing and feasibility evaluation of the self-powered, wirelessly controlled, full-scale kinetic facade panel prototypes fabricated from aluminium sheet. This study contributes to the field of hybrid kinetic facade systems through investigating approaches to fabrication, kinetic set-up and performance, and a material and economic feasibility assessment through cost and LCA.